Trimethylamine abatement in algal-bacterial photobioreactors - Pascual, Celia; Akmırza, İlker; Perez, Rebeca; Arnaiz, Esther; Munoz, Raul; Lebrero, Raquel (Springer Heidelberg, 2020)
Trimethylamine (TMA) is an odorous volatile organic compound emitted by industries. Algal-based biotechnologies have been proven as a feasible alternative for wastewater treatment, although their application to abate polluted air emissions is still scarce. This work comparatively assessed the removal of TMA in a conventional bacterial bubble column bioreactor (BC) and a novel algal-bacterial bubble column photobioreactor (PBC). The PBC exhibited a superior TMA abatement performance compared to the conventional BC. In this sense, the BC reached a removal efficiency (RE) and an elimination capacity (EC) of 78% and 12.1 g TMA m(-3) h(-1), respectively, while the PBC achieved a RE of 97% and a EC of 16.0 g TMA m(-3)center dot h(-1) at an empty bed residence time (EBRT) of 2 min and a TMA concentration ~500 mg m(-3). The outstanding performance of the PBC allowed to reduce the operating EBRT to 1.5 and 1 min while maintaining high REs of 98 and 94% and ECs of 21.2 and 28.1 g m(-3)center dot h(-1), respectively. Moreover, the PBC improved the quality of the gas and liquid effluents discharged, showing a net CO2 consumption and decreasing by ~ 30% the total nitrogen concentration in the liquid effluent via biomass assimilation. A high specialization of the bacterial community was observed in the PBC, Mumia and Aquamicrobium sp. being the most abundant genus within the main phyla identified. Graphical
Keywords: Biodegradation; Bubble column bioreactor; Microalgae-bacteria; Odor treatment; Photobioreactor; Trimethylamine